Metastabilities in Zn (O,S) - buffered Cu (In,Ga) (S,Se)2 thin film solar cells - Chua, Rou Hua (2017)
Cu(In,Ga)(S,Se) (CIGSSe) solar cells buffered with zinc oxysulfide (Zn(O,S)) have reached record cell efficiencies of 22.3%. However, the key limitation of Zn(O,S) buffered CIGSSe solar cells comes from its requirement of an extra light soaking step during fabrication, as opposed by conventional Cu(In,Ga)(Se)2 (CIGS) solar cells buffered by toxic cadmium sulfide, which reaches 21.7% cell efficiency. In this thesis, long term thermal ageing tests at 60°C and 105°C establish the difference in behavior of CdS buffered versus Zn(O,S) buffered solar cells. During these tests, n1etastability, in other words transient cell efficiency loss recoverable by light soaking, is observed in Zn(O,S) buffered solar cells but not in CdS buffered solar cells. This PhD thesis investigates the Mechanism for metastability in zinc oxysulfide (Zn(O,S)) buffered CIGSSe solar cells, and demonstrates a solution to mitigate cell efficiency loss. In the first part, long term stability tests at 60°C and 105°C were performed to compare the ageing behavior of CdS-buffered and Zn(O,S)-buffered CIGSSe solar cells. In addition to the loss of cell efficiency in Zn(O,S) buffered devices an acceleration of cell efficiency relaxation was also observed for Zn(O,S) samples that had previously undergone 1000 h 105°C thermal ageing. Whereas pristine Zn(O,S) sample relaxed in the time frame of weeks, thermally aged solar cells recovered by light soaking were seen to lose ~ 70-80% of their original efficiencies in 1-2 days, even at room temperature. X-ray photoemission spectroscopy showed an increase of sulfur in the Zn(O,S) buffer layer after thermal ageing, implying out-diffusion of sulfur from the CIGSSe absorber during the high temperature stability test. In order to understand the mechanism of cell efficiency loss, Time Resolved Photoluminescence was employed to characterize the minority carrier lifetimes of Zn(O,S) devices of different buffer ratios. Charge separation strength of the p-n junction were evaluated for Zn(O,S) devices with different [O]:[S] prepared by atomic layer deposition. Efficient charge separation was found in devices with low sulphur content [0]: [S] of 1 :0-4: 1. A biexponential decay lifetime, accompanied by high photoluminescence intensity count, was observed in relaxed devices with [O]:[S] of 2: 1 and both relaxed and light soaked devices with [0]: [S] of 1: 1. Corroborated with one-dimensional electronic band structure simulation results, it was demonstrated for the first time that minority carrier lifetime of Zn(O,S) buffered solar cells were dependent on the sulfur content of the buffer layer. The additional decay lifetime was attributed to radiative recombination in the absorber due to excessive acceptor-type defects in sulfur-rich Zn(O,S) buffer layer that caused a buildup in interface-barrier for charge transport. Having identified the detrimental effect of sulfur in the Zn(O,S) buffer on metastability, a CIGSSe device with significantly reduced n1etastability can then be fabricated. A high cell efficiency was obtained by matching the buffer composition of 11 % atomic ratio of sulfur to an CIGSSe absorber with surface sulphur/selenium ratio of 3.4. The main accomplishment of this work is to obtain a 16.5% device with negligible metastability by means of depositing a stoichiometrically controlled composition of zinc, oxygen, and sulfur onto an absorber with high surface sulfur content.